A Review of Credit Audit Procedure Implementation at KAP XYZ Surabaya: Theory and Practice - Achmad, Fadil; Acynthia Ayu Wilasittha (Universitas Bhayangkara Surabaya, 2025)
This study aims to examine the implementation of credit audit procedures applied by Public Accounting Firm (KAP) XYZ in auditing the financial statements of a Rural Bank (BPR), and to compare them with the accounts receivable audit procedures as described in academic literature. The research adopts a descriptive qualitative approach, with data collected through a review of internal documents from the accounting firm, interviews with experienced auditors, and an analysis of audit theories and guidelines related to accounts receivable found in standard textbooks. The findings indicate that the credit audit procedures implemented by KAP XYZ are generally aligned with the standard guidelines for auditing receivables. Although certain procedures—such as debtor balance confirmations and the inspection of promissory notes—were not applied, this was due to their incompatibility with the operational characteristics of BPRs. These findings suggest that KAP XYZ has effectively adapted its audit procedures to remain relevant and efficient in identifying risks and ensuring the reliability of the financial information presented by the BPR.